Can Botulinum Toxin Type E Serve as a Novel Therapeutic Target for Managing Chronic Orofacial Pain? - Sung-Koog Jung; Yu-Mi Kim; Min-Jeong Jo; Jo-Young Son; Jin-Sook Ju; Min-Kyoung Park; Min-Kyung Lee; Jae-Young Kim; Jeong-Sun Nam; Dong-Kuk Ahn (Toxins)
The existing literature offers limited experimental evidence on the role of botulinum neurotoxin type E (BoNT-E) in pain transmission. The present study investigated the antinociceptive effects of subcutaneously administered BoNT-E in chronic orofacial pain conditions. This study used orofacial formalin-induced pronociceptive behavior and complete Freund’s adjuvant (CFA)-induced thermal hyperalgesia as inflammatory pain models in male Sprague Dawley rats. A neuropathic pain model was also developed by causing an injury to the inferior alveolar nerve. Subcutaneously administered BoNT-E (6, 10 units/kg) significantly reduced nociceptive behavior during the second phase of the formalin test compared to that of the vehicle treatment. These doses similarly alleviated thermal hypersensitivity in the CFA-treated rats. Moreover, BoNT-E (6, 10 units/kg) markedly attenuated mechanical allodynia in rats with an inferior alveolar nerve injury. At a dose of 10 units/kg, BoNT-E produced antinociceptive effects that became evident 8 h post-injection and persisted for 48 h. Notably, BoNT-E (10 units/kg) significantly reduced the number of c-fos-immunostained neurons in the trigeminal subnucleus caudalis of rats with an inferior alveolar nerve injury. In comparison, intraperitoneally administered gabapentin (30, 100 mg/kg) demonstrated significant mechanical anti-allodynic effects but exhibited lower analgesic efficacy than that of BoNT-E. These findings highlight the potential of BoNT-E as a therapeutic agent for chronic pain management.